2013 13th International Conference on ITS Telecommunications (ITST) 2013
DOI: 10.1109/itst.2013.6685559
|View full text |Cite
|
Sign up to set email alerts
|

Security of Wi-Fi on-board intra-vehicular communication: Field trials of tunnel scenario

Abstract: Wireless communications are increasingly-often selected as a cable replacement for on-board vehicular networks. When a wireless technology implements safety critical application, cryptographic countermeasures are required. This paper describes the impact of security on intra-vehicular communication in a real tunnel scenario, e.g. for urban transit or mining vehicles where the usage of security is mandatory in order to maintain the system safety. The measurement campaign was carried out in a sport ski-tunnel us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In this Section, we collect some types of attacks on IV communications often discussed in the literature (see, for instance, [29], [30], [31]) 4 . Consider an adversary onboard the train (see Figure 11) with his laptop that performs various attacks against IV Wi-Fi communications.…”
Section: Threat Models For IV Communicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this Section, we collect some types of attacks on IV communications often discussed in the literature (see, for instance, [29], [30], [31]) 4 . Consider an adversary onboard the train (see Figure 11) with his laptop that performs various attacks against IV Wi-Fi communications.…”
Section: Threat Models For IV Communicationsmentioning
confidence: 99%
“…To do so, Soderi et al [30], [31], [29] proposes using Host Identity Protocol (HIP) for industrial and railway applications to secure the IV communication system architecture.…”
Section: E Building a Secure Conduit: An Approach Based On Host Ident...mentioning
confidence: 99%
See 2 more Smart Citations
“…HIP with the Base Exchange (BEX) initial stage establishes a Secure Association (SA) between end-nodes, then both hosts use IP Security (IPSec) in order to exchange data via a secure tunnel, as shown in Figure 2. Measurements campaign in a tunnel scenario has shown that HIP IPSec is a promising protocol to secure intra-vehicular communications in terms of throughput, jitter and packet loss [7].…”
Section: A Attack To Wi-fi Based Dcsmentioning
confidence: 99%